General Equilibrium Models and Application of them in Lithuania - Kalinauskas, Žilvinas (Ekonomika, 1999)
In this article there are described General Equilibrium Models (GEM) for Sweden and Lithuania. The Swedish model is built on stable microeconomic foundations, and almost all relationships are derived from optimising behaviour by the agents concerned. At first, the model is specified in real terms, but with output determined from the supply side. In the short-run equilibrium the output price of the single domestic good in the model is determined by the interaction of supply and demand in the goods market. The long-run equilibrium may be characterised as an “Europe equilibrium”, with the domestic rate of inflation equalling the foreign rate. When money is introduced the real and financial sides of the economy are seen to be linked via the government budget deficit as well as through the equilibrium condition in the money market.The GEM for Lithuanian economy is based on the Social Accounting Matrix (SAM) for year 1995. For economic analysis purpose it is used less advanced H. H. de Haan model for Hungarian economy. Especially having in mind that this model is more ready for use and rather attractive to start with. In this article there are presented some scenarious of economic development: energy sector’s activity, fiscal and monetary policies’ instruments impact on Lithuanian economy.